Insulin Resistance and Hypogonadism (Delta Medical College Journal, 2013)
Backgound: The number of hypogonads is increasing day by day. It may be due to sedentary life style with increased obesity, increased tension or stressed lifestyle among all groups of populations. Visceral obesity is associated with insulin resistance, diabetes mellitus and also with hypogonadism. Objective: This study was carried out to determine the proportion of insulin resistance among male subjects with hypogonadism in different age groups along with status of erectile quality among diabetics and non diabetics. Materials and method: This cross sectional study among 161 adult male subjects aged ? 20 to ? 60 years were purposively selected from Bangladesh Institute of Research and Rehabilitation in Diabetes Endocrine and Metabolic Disorders (BIRDEM), Dhaka, Bangladesh between May 2009 to September 2010. Glycemic status and insulin resistance (by HOMA-R) were done and relevant history were documented. Results: The highest proportion (38.9%) of hypogonadism was in ? 50 years age group whereas highest proportion (39.6%) of the eugonads was in the age group of 40 to 49 years. More than half of the hypogonad subjects had weak erectile quality (54.0%) which were followed by absent erectile quality in 32.7% and 13.3% subjects had normal erectile quality. Among the eugonad subjects 41.7% had normal erectile quality, 41.6% subjects had weak erectile quality and 16.7% subjects had no erectile quality. More than ninety percent of the hypogonad subjects and about 60% of the eugonad subjects had insulin resistance. The average HOMA-R was more in the subjects with hypogonadism with diabetes which was highly significant (p-value < 0.001). Conclusion: Hypogonadism is associated with insulin resistance.DOI: http://dx.doi.org/10.3329/dmcj.v1i1.14968 Delta Med Col J. Jan 2013;1(1):3-7